Characterisation of helical structure in AFM micrographs of a trimer of the peptide sequence (ValGlyGlyValGly)1. (7th April 2014) - Castle, James Eric; Ibris, Neluta; Salvi, Anna Maria; Moscarelli, Pasquale; Bochicchio, Brigida; Pepe, Antonietta; Abel, Marie‐Laure; Rossi, Antonella; Watts, John F.
<x xml:space="preserve">Abstract</x> Studies by atomic force microscopy of a set of helical fibres formed within the same period of time from the amyloidogenic peptide, (VGGVG)3 show that there is a characteristic increment in diameter, suggesting that the helices are formed from multiple layers. Measurement of the height to pitch ratio suggests that each succeeding layer forms on top of the previous winding and does not fit into the gap between the turns. Dimensions are given for the increment per layer and for the pitch of the helices. Copyright © 2014 John Wiley & Sons, Ltd.